BUDIDAYA JAMUR PERUSAK KAYU I. PENGARUH PENAMBAHAN DEDAK TERHADAP PRODUKSI JAMUR TIRAM - Sihati Suprapti (Jurnal Penelitian Hasil Hutan, 1988)
Oyster  mushroom   (Pleurotus ostreatus) was cultivated  on sawdust  of  four  wood  species,   i.e.  teak  (Tectona  grandis L.f.), rubber   (Hevea  brasiliensis  .Muell.   Arg.),    kemang  (Mangifera  caesia  Jack)  and  meranti   merah  (Shorea  johorensis Foxw.)   mixed   with  rice  bran containing  5 %, 10 %, 15 %, 20 %, 25 % by  weight  and  distilled  water, The  substrate  was cooled  after  autoclave  sterilization   before  being inoculated  with  pure  culture  of oyster  mushroom. The mature  mushrooms were harvested  daily  after   the growth  of  fruiting  body.Relative   high  yield   was obtained   from   rubber  (146.92 g) and  kemang  (122.77 g),  the lower  yield  was obtained from  teak  (73.84 g) and the lowest  from  meranti  merah (58.82   g) per 500 g media.     .Rice  bran supplement seems  to improve mushroom yield. The  lowest  yield  i.e;  obtained   from  sawdust  substrate mixed  with  5 % rice bran  (65.78 g).  Rice bran supplementation  of 10 -  25 % gave non significant  different  yield  (80.30  - 88.86   g) per  500 g media.The  average Biological  Efficiency (BE)  of entire  treatments   were  obtained  from  rubber  64.27 % (45.24  - 79.84 %) and  kemang 61.66  % (56.84  - 74.25 %).  The  lower  BE  was obtained  from  teak 29.53  % (25.86 - 33.92  %) and meranti merah  24.70 % (0 -  40.22 %).